Pengaruh Sosial Media Marketing Facebook terhadap Minat Beli Konsumen Yab Showroom Gorontalo - Siti Nur Afni Saman; Muchtar Ahmad; Yulinda L. Ismail (Economic Reviews Journal, 2024)
This research aims to find out how much influence Facebook Social Media Marketing has in increasing Consumer Buying Interest at YAB Showroom Gorontalo. This type of research uses quantitative methods, by distributing questionnaires to 63 respondents using the Slovin formula calculation. The analysis used in this research uses simple linear regression analysis. The results of this research show that the Facebook Social Media Marketing variable has a significant positive effect on Purchase Interest with a significance level of 0.001 < 0.05 and a value of tcount > ttable, namely 3,330 > 3,231. The magnitude of the influence of the coefficient of determination R square is 15.4% while the remaining 84.6% is explained or described by other independent variables which are not included in this research model.